Strategy Formulation and Action Plan Based On Customer Perception (Case Study: Gianni\'s Cafe) - Nugraha, Nandi Wardhana; Toha, Mohamad (The Indonesian Journal of Business Administration, 2015)
Abstract.Gianni's Café is one of western food restaurant in Bandung that was established in 2007. In the midst of many competitors both direct and indirect competitors, Gianni's Café is required to survive and grow. This study aims to formulate effective and efficient business strategy in order to achieve the appropriate market target and formulate an action plan to improve important factors based on customer perceptions so as able to keep and attract customers.The framework uses a strategic triangle, which consists of customer-base, competitor-base, and corporate-base. They were analyzed by the support of quantitative data that taken by spreading questionnaires to 100 potential customers and 100 existing customers of Gianni's Café. The questionnaire contains 16 customer buying criteria that were obtained through interviews with several general respondents at the beginning of this research. The result of questionnaires was processed by dendrogram using word's procedure to determine the number of clusters of Gianni’s Cafes’ customer. Then the process of cluster analysis was conducted based on the level of income. On the customer-base, it was obtained 4 clusters of customers who visit the restaurant based on income. On the company-base, it was known the strengths of Gianni's Café performance compared to competitors based on 16 customer buying criteria within the four clusters. On the competitor-base, it is known the strengths of competitor performance compared to Gianni's Cafe based on 16 customer buying criteria within the four clusters. Based on those three considerations, the appropriate market target and business formulations were then chosen.From result of the study, it was obtained that the appropriate market target for Gianni's Café is a segment of customers that has an income per month over 10 million rupiahs. To target these segments, there are six key factors that should be improved and adjusted by Gianni's Café. These six key factors become the value proposition for Gianni's Café and are derived to be key activities to maintain and attract new customers. Lastly, it can be compared the existing business model canvas to the ideal business model canvas which is to be implemented by Gianni's Café.Key word: Strategic Triangle, Customer-Base, Competitor-Base, Corporate-Base, Restaurant Business, Business Model Canvas